Electromechanical instabilities in periodic dielectric elastomer composites. (15th May 2020) - Jandron, Michael; Henann, David L.
Abstract: Several types of electromechanical instability emerge in periodic dielectric elastomer (DE) composites – either limiting the range of electromechanical actuation or providing an opportunity to harness instabilities for enhanced functionality. The electromechanical pull-in instability – extensively studied in monolithic DEs – is also encountered in periodic DE composites, and additional instability types – microscopic, macroscopic, and interfacial instabilities – arise in DE composites. For general DE composites subjected to arbitrary electromechanical loading, numerical simulation is required to detect all types of instability. In this paper, using a finite-element-based numerical simulation capability, we consider electromechanical instabilities in DE composites consisting of periodic lattices of aligned circular-cross-section fibers embedded in a matrix. We report on several types of electromechanical instabilities that are known to occur in this type of DE composite: (1) pull-in, (2) microscopic, (3) macroscopic, and (4) interfacial instabilities, while surveying a comprehensive parameter space. Namely, the roles of shear modulus contrast, electric permittivity contrast, fiber volume fraction, chain-locking behavior, mechanical prestress, prestretch, and confinement are considered. The result is an overarching view of the instability landscape in periodic, fiber-based DE composites. We conclude by showing that microscopic instabilities may be harnessed to invoke electric-field-triggered pattern transformations in certain cases.